Extraction behavior of As, Pb, and Zn from mine tailings with acid and base solutions - Yang, Jung-Seok; Lee, Ju Young; Baek, Kitae; Kwon, Tae-Soon; Choi, Jaeyoung (ELSEVIER SCIENCE BV, 2009)
The aim of this study was to investigate the extraction behavior of As, Pb, and Zn from mine tailings for considering the feasibility of soil washing. Extraction of metals was studied for different extractant closes, solid/liquid ratios, and equilibrium times. Generally, high extraction efficiency was achieved with HCl, H3PO4, and H2SO4, while H2SO4 proved to be problematic with respect to Pb. NaOH was found to be favorable in removing As, while it was not effective at extracting Pb and Zn. With optimum conditions, which were a 1:5 solid-liquid ratio and 2 h of extraction time, 0.5 M of HCl extracted 21.1-72.5%, 9.9-86.5%. and 6.1-74.1% of As, Pb, and Zn, respectively. The power and Elovich function were adequate to describe adsorption kinetics. These results suggest that HCl and NaOH could be used to effectively extract all metals without selectivity and As with selectivity, respectively, in mine tailings and could be used for the design of soil washing process. (C) 2009 Elsevier B.V. All rights reserved.